VIOLENCE AGAINST WOMAN IN EKA KURNIAWAN’S NOVEL CANTIK ITU LUKA - Fhadila, Riska; Manugeren, M.; Purwarno, Purwarno (JOURNAL OF LANGUAGE, 2024)
This study delves into the theme of violence against women in Eka Kurniawan's novel Cantik Itu Luka  based on gender roles and violence experienced by women during and after Japan's periods of pre-independence and post-independence. The study aims to identify and analyze the various forms of violence and the underlying factors contributing to social deviance towards the protagonist, utilizing theoretical framework of cultural forms of violence by means of descriptive qualitative research to uncover the social phenomena of violence against women.  The study concludes that the novel provides a profound exploration of gender-based violence, encompassing direct, structural, and cultural dimensions of violence. The protagonist embodies the trauma of direct violence witnessed during the Japanese occupation, highlighting the gender-based discrimination prevalent against women. Structural violence is evident in societal disparities, while cultural violence permeates the narrative through deeply rooted attitudes and beliefs. The  novel also  delves into various aspects of discrimination faced by female characters in educational, domestic, and professional settings. The intertwining of historical contexts and personal stories within the novel serves as a potent commentary on women's ongoing struggles for justice and the enduring effects of discrimination. Ultimately, Cantik Itu Luka emerges as a poignant exploration of the intricate layers of gender-based violence and the resilience exhibited by women in confronting oppression.